The impact of social media marketing on customer loyalty by achieving customer satisfaction - BILEL, NETTOUR; LYES, BOUDJAADA (The journal of contemporary issues in business and government, 2023)
When marketing tourism services, the corporation always seeks to make the best use of social media in order to achieve customer satisfaction and achieve sustainable loyalty to the customer. Accordingly, through this research paper, the role of customer satisfaction as a mediator between relying on social media in marketing to achieve customer loyalty is studied, and a sample of customers of tourist agencies of Skikda state was relied upon, where a simple random sample of 180 respondents was selected. After distributing and retrieving the questionnaire, we used 158 questionnaire after excluding the invalid for analysis, the retrieved data was analyzed using the statistical program smart-pls4, and the results of modeling using structural equations showed that there is a relationship between marketing using social media and customer loyalty through total customer satisfaction.